PP10 How senior paramedics determine a futile resuscitation in pulseless electrical activity out of hospital cardiac arrest: a mixed methods study. Issue 10 (25th September 2020) - Coppola, Ali; Black, Sarah; Endacott, Ruth
Abstract : Background: Pulseless electrical activity, a non-shockable cardiac arrest, is treated using advanced life support resuscitation. When resuscitation fails, evidenced-based guidelines are limited on when to stop resuscitation. This led to one UK Ambulance Service developing a local guideline for senior paramedics to cease resuscitation when considered futile. The aim of this study was to examine clinical, patient and system factors of a futile resuscitation for pulseless electrical activity and how senior paramedics apply these factors to the decision-making process. Design and Methods: An explanatory sequential mixed method design conducted in a single UK Ambulance Service. Cessation of resuscitation data was retrieved for all adult patients suffering an Out of Hospital Cardiac Arrest from 1st December 2015 to 31st December 2018. Cases subject to a coronial or police investigation were excluded. Senior paramedics made decisions to cease resuscitation for 50 patients at the scene and these were reviewed in detail. Interviews were conducted with six senior paramedics, who provide telephone clinical support to on-scene paramedics. Results: The mean patient age was 78 years, the majority were male (n=30, 60%) had a witnessed collapse (n=37, 74%) and had a PEA rate below 50 (n=46, 92%). There were no significant associations between patient demographics and clinical or system factors. Themes arising from paramedic interviews included concepts that defined futility, the impact of decision-making, conflicting views and supportive clinical decision tools. Conclusion: Whilst there were no significant associations between variables, senior paramedics balanced patient survival with resuscitation futility by interpreting key factors, such as patient demographics and clinical factors. This multifactorial approach questions termination of resuscitation based on clinical factors alone. It identifies a group of PEA patients, when resuscitation is not successful, may be considered for termination of resuscitation. Research using a larger sample is warranted to explore the validity of these criteria. Acknowledgements: The authors would like to thank Professor Jonathan Benger for his valuable input and guidance as the educational supervisor for this study. J. Lynde and H. Trebilcock for quantitative data extraction. L. Tremayne and E. Freeman, qualitative data coding. Thank you to all the paramedics who participated.